Z33 Hasselt: Hortus Conclusus as a Model for an Urban Interior - Bie Plevoets; Shailja Patel (Interiority, 2021)
This contribution reviews the recent renovation of Z33—House for Contemporary Art, Design and Architecture in Hasselt, Belgium—in the light of its unique implementation of different levels of interiority. The institute is housed in the former beguinage, a site with a rich and layered history and one of the few green public spaces in the city centre. The intervention by architect Francesca Torzo builds further on and strengthens the existing qualities of the site through a creative process of copying and improving. By doing so, she changed the overall appearance of the beguinage, strengthening its quality as an enclosed public space—an intimate yet collective hortus conclusus.